Estratégias de adubação orgânica em pastagem de Brachiaria brizantha cv. Marandu com M Stylosanthe spp no bioma cerrado - Silva, Luiz Henrique Xavier da (2017)
The aim of this work was to evaluate dry matter yield (DMY), chemical composition and contribution of legumes in Brachiaria brizantha cv. Marandu pasture intercropped with a mixture of Stylosanthes spp. cultivars (Mineirão, Campo Grande and Bela) exposed to organic and conventional management during three years in two adjacent areas (Oxisol) with or without green manure (Crotalaria juncea). The experimental design was randomized blocks in split split plot with 3 repetitions and 3 factors: fertilizing, use of legumes and use of fungus. In the plot were made three types of soil fertilization management (no fertilization (Control), conventional management (CM) and organic management (OM) fertilization); in the split plot two planting management (with and without pigeon peas); in the spli split plot (with and without fungus). Three months before planting it was applied 2 t ha-1 of dolomitic limestone and 1 t ha-1 of gypsum and then green manure area was cropped using Crotalaria juncea to guarantee the organic Matter and N source. At planting OM was performed with N, K and P sources such as chicken manure (1.5%N), thermopotassium (6%K2O) and thermophosphate (12%P2O5) in amounts of 6.7 ha-1, 2 t ha-1 and 1 t ha-1, respectively. For CM treatment it was used potassium chloride (60%K2O), triple superphosphate (46%P2O5) and urea (46%N) totaling 200, 260 and 217 kg.ha-1, respectively. PMS did not present significant differences between the treatments studied. The organic management favored in both Brachiaria and Stylosanthes better chemical composition and nutritional quality. The multivariate analysis technique using the principal components analysis method was more efficient in the expressive determination of Brachiaria brizantha cv Marandu variables, with non - random behavior of the groups.